2009
DOI: 10.1111/j.1399-0039.2009.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of TNF‐α and its soluble receptors sTNFR1 and sTNFR2 in patients with coronary artery disease

Abstract: Tumour necrosis factor alpha (TNF-alpha) is implicated in post-ischemic myocardial dysfunction. Two distinct TNF-alpha receptors are shed from cell membranes and circulate in plasma as soluble sTNFR1 and sTNFR2 proteins. The aim of the study was to establish factors associated with plasma concentrations of TNF-alpha and its receptors in patients with coronary artery disease (CAD). Since adenosine inhibits the expression of TNF-alpha, two functional polymorphisms in genes encoding enzymes participating in adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 35 publications
6
33
0
3
Order By: Relevance
“…Soluble TNFR1 was shown to be cross-sectionally associated with cardiometabolic risk factors in a study of patients with coronary artery disease: elevated uric acid levels, lower HDL cholesterol, metabolic syndrome, diabetes and heart failure [21]. In accordance with our findings where sTNFR1 was associated with cardiovascular mortality after adjustments for CRP and IL-6, sTNFR1 but not IL-6 and CRP was associated with left ventricular mass in a study of over 600 patients with stroke [22].…”
Section: Comparisons With Previous Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…Soluble TNFR1 was shown to be cross-sectionally associated with cardiometabolic risk factors in a study of patients with coronary artery disease: elevated uric acid levels, lower HDL cholesterol, metabolic syndrome, diabetes and heart failure [21]. In accordance with our findings where sTNFR1 was associated with cardiovascular mortality after adjustments for CRP and IL-6, sTNFR1 but not IL-6 and CRP was associated with left ventricular mass in a study of over 600 patients with stroke [22].…”
Section: Comparisons With Previous Studiessupporting
confidence: 88%
“…The association between sTNFR1 and cardiovascular mortality could be explained by its direct atherosclerotic effects by being a marker of a higher systemic inflammatory state [21,25]. Inflammation does not only initiate the formation of the atherosclerotic lesion, but can also be involved in plaque rupture; the final trigger of most thrombotic and atherosclerotic events [31].…”
Section: Possible Mechanisms For the Observed Associationsmentioning
confidence: 99%
“…In addition, Yamawaki et al demonstrated a vasodilating effect of omentin on isolated blood vessels, suggesting omentin involvement in endothelial function [14] . There have been several reports showing that other adipokines, such as adiponectin [15][16][17] , resistin [17][18][19][20] , leptin [19] , visfatin [21][22][23] , TNF-α [24] , and IL-6 [25] , are related to inflammation and coronary artery disease (CAD). We hypothesized that omentin-1 might be implicated in CAD due to a possible association with inflammation and endothelial function.…”
Section: Introductionmentioning
confidence: 99%
“…The level of sTNFR2 in the circulation could therefore be interpreted as the degree of activation of TNF-α signalling in the tissues, making sTNFR2 an interesting parameter for TNF-α activation in the tissues. High levels of sTNFR2 in serum have been documented in multiple inflammatory pathologies 29,30 . Metabolic syndrome and diabetes are also associated with higher plasma concentrations of TNFalpha and its receptors 31 .…”
Section: Discussionmentioning
confidence: 99%